Australian New Year's PyroCb Impact on Stratospheric Composition. Issue 24 (13th December 2020) - Schwartz, Michael J.; Santee, Michelle L.; Pumphrey, Hugh C.; Manney, Gloria L.; Lambert, Alyn; Livesey, Nathaniel J.; Millán, Luis; Neu, Jessica L.; Read, William G.; Werner, Frank
Abstract: Following the Australian New Year's pyrocumulonimbus complex between 29 December 2019 and 4 January 2020, the Aura Microwave Limb Sounder (MLS) observed a plume with unprecedented enhancements of H2 O and biomass‐burning products (CO, HCN, CH3 Cl, CH3 CN, and CH3 OH) in the lower/middle stratosphere, accompanied by depressions in stratospheric species (O3 and HNO3 ). The plume persisted for ∼110 days, circling the globe twice while ascending to 5.62 hPa (∼35 km). Air masses drawn off the main plume moved toward the developing Antarctic polar vortex but do not appear to have penetrated it. Comparison of species in the plume requires consideration of their measurements' spatial resolutions and background abundances. The apparent decay of some long‐lived plume constituents is largely attributable to their coarsening spatial resolution with height, which reduces observed peak values. Differing HCN/H2 O signatures indicate that multiple early plumes originated from different stratospheric injection events. Plain Language Summary: Severe wildfires can trigger vigorous smoke‐infused thunderstorms called pyrocumulonimbuses (pyroCbs) that rapidly loft polluted air from the surface, in the most extreme cases depositing it in the lower stratosphere ( ≳ 14 km altitude). Three times in the past 16 years, long‐lived stratospheric plumes from major pyroCbs have been observed in a suite of biomass‐burning products measured by the Microwave Limb Sounder on NASA's Aura satellite. Dark smoke in these plumes absorbs sunlight; the plumes rise because they are warmer than the surrounding air. The third, and by far the largest, of these plumes was produced by an extraordinary set of pyroCbs in Australia between 29 December 2019 and 4 January 2020, collectively known as the Australian New Year's event (ANY). The ANY plume core remained remarkably compact, circling the globe twice while rising from ∼14 km to ∼35 km altitude over a period of 4 months. Record‐setting concentrations of five biomass‐burning products were measured by MLS throughout the lower stratosphere. Plume fragments tended to move south but do not seem to have influenced ozone‐hole chemistry. Differing gas mixtures suggest that several plumes in the first month originated in different pyroCbs. Careful comparison of plume gases requires consideration of the blurriness of the measurements. Key Points: MLS observed record‐high stratospheric trace gas abundances from the 2019–2020 Australian New Year's fires rising to 5.6 hPa over 110 days Plume fragments moved poleward but do not appear to have entered the developing Antarctic winter vortex Analysis of correlations between constituent measurements requires consideration of their spatial resolutions